2018
DOI: 10.1155/2018/2163526
|View full text |Cite
|
Sign up to set email alerts
|

Food Integrity and Food Technology Concerns in Canada: Evidence from Two Public Surveys

Abstract: Food integrity and food technologies both generate public concerns. There is little research to show the interactions between those concerns in particular samples, especially in Canada. In this paper, data from two national online samples are used to examine an aggregate of food integrity concerns, genetic modification in food, and food nanotechnology concerns in the Canadian public. A variety of trust, health, environmental, and science attitude variables are used to help explain the concerns that vary across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Another study conducted in the USA, found that attitudes were generally positive toward nanotechnology, with more than half of individuals indicating that nanotechnology will improve their quality of life (Gardner et al, 2010). Although attitudes in previous studies seem to be more optimistic regarding nanotechnology compared to GM foods, this may be due to the fact that nanotechnology is less well-known to the general public (Goddard et al, 2018, Steenis, 2016.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Another study conducted in the USA, found that attitudes were generally positive toward nanotechnology, with more than half of individuals indicating that nanotechnology will improve their quality of life (Gardner et al, 2010). Although attitudes in previous studies seem to be more optimistic regarding nanotechnology compared to GM foods, this may be due to the fact that nanotechnology is less well-known to the general public (Goddard et al, 2018, Steenis, 2016.…”
Section: Discussionmentioning
confidence: 98%
“…Controversy and confusion are common themes regarding nanotechnology and GMOs (Goldbas, 2014; Veeman et al , 2005; Knight , 2009; Chmielewski et al , 2017; Giles et al , 2015; Gardner et al , 2010; Diefes-Dux et al , 2007; Siegrist., et al ,2007; Siegrist et al , 2009; Sarno, 2016). The factors related to the controversy and confusion include lack of consumer knowledge, sociodemographic factors, environmental concerns and risk benefit perceptions (Yue et al , 2015; Giles et al , 2015; Goddard et al , 2018; Riberio et al , 2016; Sheehy, 1998; Costa-Font et al , 2008; Boccia, 2016; Sarno, 2016; Boccia et al , 2018). A Canadian study indicated that a majority of the participants felt as though there were many risks associated with GMOs, including that they were unnatural, and not necessary in Canada (Lukosiute and Senekevic-Petrauskaite, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In response, production standards have been developed that 88 follow the principles of hazard analysis and critical control point (HACCP) systems and 89 apply a systems-based approach to managing food safety (Gil et Food integrity has been defined as ensuring that food which is offered for sale is 98 not only safe and of the nature, substance and quality expected by the purchaser, but also 99 considers other aspects of food production, such as the way it has been sourced, procured 100 and distributed and being honest about those elements to consumers (Elliott, 2014). Thus, 101 developing supply chain systems and standards that assure food integrity will enhance 102 food safety, authenticity, quality, and increase consumer trust in product claims (Kleboth 103 et al 2016;Goddard et al 2018). Integrity in the horticulture supply chain is driven by 104 consumers who demand that the produce they purchase is firstly, what it purports to be 105 (product integrity); secondly is produced in line with defined standards (process 106 integrity); thirdly that these standards address ethical corporate behaviour (people 107 integrity); and finally the data associated with the produce (data integrity) is valid and 108 reflects the intrinsic and extrinsic characteristics of the product (Manning, 2016;109 Manning, 2018).…”
Section: Take Inmentioning
confidence: 99%
“… Cox and Evans (2008) developed a psychometric tool to identify levels of neophobia in relation to technology, which is based on the food neophobia scale first developed by ( Pliner and Hobden, 1992 ). The FTNS is recognized as a valid and accurate tool for assessing consumer fear by focusing on the food technology rather than the food product ( Henriques et al, 2009 ; Evans et al, 2010 ; Matin et al, 2012 ; Goddard et al, 2018 ). Yang and Hobbs (2020) analyzed information framing effects in consumer perception among GEd (CRISPR-Cas9).…”
Section: Introductionmentioning
confidence: 99%